Force-field dependence of chignolin folding and misfolding: comparison with experiment and redesign - Kührová, Petra; De Simone, Alfonso; Otyepka, Michal; Best, Robert B (Biophysical journal, 2012)
We study the folding of the designed hairpin chignolin, using simulations with four different force fields. Interestingly, we find a misfolded, out-of-register, structure comprising 20-50% of the ordered structures with three force fields, but not with a fourth. A defining feature of the misfold is that Gly-7 adopts a β(PR) conformation rather than α(L). By reweighting, we show that differences between the force fields can mostly be attributed to differences in glycine properties. Benchmarking against NMR data suggests that the preference for β(PR) is not a force-field artifact. For chignolin, we show that including the misfold in the ensemble results in back-recalculated NMR observables in slightly better agreement with experiment than parameters calculated from a folded ensemble only. For comparison, we show by NMR and circular dichroism spectroscopy that the G7K mutant of chignolin, in which formation of this misfold is impossible, is well folded with stability similar to the wild-type and does not populate the misfolded state in simulation. Our results highlight the complexity of interpreting NMR data for small, weakly structured, peptides in solution, as well as the importance of accurate glycine parameters in force fields, for a correct description of turn structures.
Keywords: simulace molekulární dynamiky; sekundární struktura proteinů; sbalování proteinů; oligopeptidy; software; Oligopeptides; Protein Structure, Secondary; nukleární magnetická rezonance biomolekulární; Molecular Dynamics Simulation; Software; Protein Folding; Nuclear Magnetic Resonance, Biomolecular